ANALISIS BIAYA DAN TENAGA KERJA PADA BEBERAPA KILANG PENGGERGAJIAN DI SUMATERA SELATAN - Sylviani Sylviani; Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1990)
The result of research on several sawmills in South Sumatera  showed that average   level of manager productivity is 7.563 Cu.m/man/annum, administration productivity is  3.220 Cu.m/man/annum, tecnician productivity is 74 Cu.m/man/annum. Average labor   requirements are 9 men/1.000 Cu.m  of  the  design  capacity  and  10  men/1.000 Cu.m  of  raw material.Cost of  production of  sawntimber   showed  an average  of  Rp  184.808,-/Cu.m, in which  the processing  cost  alone ranked  high  up  to an average of  83 %, marketing  cost 10 %,  and general cost  7 %. Profit  generated of  each  mill per annum  ranged from  Rp 891.060.692,- to Rp  3.165.279.700,- or equivalent   to an average  of  Rp  80.053  per  Cu.m.